Mitigating impacts of disaster through community resilience : whakawhanaungatanga vs. zombies : an exegesis presented in partial fulfilment of the requirements for the degree of Masters of Design at Massey University, Wellington, New Zealand - Koedijk, Paige (Massey University, 2025)
This research contributes to the field of disaster risk reduction by utilising visual storytelling to emphasise the critical role of resilient communities in mitigating the impacts of climate-accelerated disasters, which disproportionately affect vulnerable populations. The Peninsula, a fictional pānui, explores the mātauranga Māori principle of whakawhanaungatanga through the depiction of ordinary members from the Miramar Peninsula community in tongue-in-cheek survival situations during an ongoing zombie catastrophe. Leveraging Wellingtonians’ appreciation for b-horror/humour storytelling seen in productions such as What We Do in the Shadows and Wellington Paranormal, the use of humour and the spectacle of a zombie context is an engaging narrative experience for readers to consider their contributions within their community in an emergency. Some social change campaigns have gained viral levels of success through the use of evocative visuals and narratives to resonate with the public, as seen in Aotearoa’s COVID-19 infographics and the CDC’s 2011 zombie-themed hurricane information. The zombie as a narrative device functions as a versatile symbol for political or socio-economic commentary, serving in this research as a “trojan-horse” for conveying emergency management information with a community focus. The social collaboration illustrated in The Peninsula mirrors the real world advantage of community resilience throughout the phases of an emergency. The design output is explored through affective design and developed through iterative cycles of “inquiry by design” methodologies and implementing community-based social marketing strategies.
Copyrightholders of any copyrighted images may use the Take Down Request link below to request their removal.
Keywords: whakawhanaungatanga; resilient communities; disaster risk reduction; affective design; storytelling; humour; Zombies; 330316 Visual communication design (incl. graphic design); 350703 Disaster and emergency management